Distance hardware laboratory Part 1 - Goh, Joel Jun Ming (2016)
The pervasive usefulness of distance learning has resulted in a widespread interest for use in various institutions for various fields. However, current distance learning methods for teaching certain aspects, such as hardware design, are limited in their functionality and usability. Hence, this project aims to develop a more modular and usable medium for remote distance learning of hardware core concepts, at a low added cost. In this project, a hardware based laboratory experiment is used as the subject for developing the hardware remote distance system. The remote distance laboratory system involves a remote PC host, with essential software such as Matlab, connected to an Arduino Uno R3 to enable digital control on a sample. In addition, multiple oscilloscopes were connected to the remote PC host, to enable the user to observe the actual effects of signal processing at various points of the sample circuit, using the open-source OpenChoice Desktop application installed on the PC host. The overall remote distance laboratory is designed to be modular and functional for the hands-on learning of hardware, with the added advantage of being remotely accessible. The sample laboratory experiment works successfully with the remote distance learning system, which could be accessed on-site within campus and through a VPN connection from external networks, through the Windows Remote Desktop Connection. Besides, there are several challenging points to be addressed, such as improving the software user interface and usefulness of the system, power management, and the security concerns while using the system.